Preparation and characterization of a novel colorimetric indicator film based on gelatin/polyvinyl alcohol incorporating mulberry anthocyanin extracts for monitoring fish freshness. (December 2019) - Zeng, Ping; Chen, Xiong; Qin, Ya-Ru; Zhang, Ye-Hui; Wang, Xu-Ping; Wang, Jing-Yu; Ning, Zheng-Xiang; Ruan, Qi-Jun; Zhang, You-Sheng
Abstract: This work aimed to develop a novel colorimetric indicator film for monitoring of food freshness based on gelatin/polyvinyl alcohol matrix incorporated with anthocyanin extracts from mulberry. The color of anthocyanin extracts solutions obviously changed from bright red to dark green in the pH range of 2.0–11.0. FTIR spectra and isothermal titration calorimetry showed that the anthocyanin extracts were successfully combined with gelatin/polyvinyl alcohol matrix by hydrogen binding and electrostatic interaction, which enhanced the stability of anthocyanin. The scanning electric microscopy showed that the compatibility between polyvinyl alcohol and gelatin were improved owing to the addition of anthocyanin extracts. With the anthocyanin extracts addition from 0 to 45 mg/100 mL mixed solution, the tensile strength decreased from 30.80 to 21.01 MPa and the elongation at break increased from 589.22% to 905.86%. The color response of film in buffer solution of different pH were in accordance with anthocyanin extracts solutions, and its color changes were clearly visible with naked eye. Finally, the film was evaluated by a test on monitoring fish spoilage, which presented visible color changes due to volatile nitrogenous compounds formed over time. These results showed that this developed film could be used as an effective method for the monitoring of food freshness. Graphical abstract: Unlabelled Image Highlights: A colorimetric film was developed by using gelatin, PVA and mulberry anthocyanin. The anthocyanin stability was enhanced by combining with film matrix. The mechanical properties of films were improved due to the addition of anthocyanin. Color changes of film in buffer solution of different pH were visible with naked eye. The film could be used as an effective method for the monitoring of fish spoilage.